Revisiting the supratrigeminal nucleus in the rat. (2nd June 2016) - Fujio, T.; Sato, F.; Tachibana, Y.; Kato, T.; Tomita, A.; Higashiyama, K.; Ono, T.; Maeda, Y.; Yoshida, A.
Highlights: Rat supratrigeminal nucleus (Vsup) could be cytoarchitectonically identified. Location of Vsup in the present study was different from that in earlier rat studies. Vsup received many terminals of primary afferents innervating jaw-closing muscles. Vsup neurons are possibly arranged with loose somatotopy. Vsup was also identified by masseter nerve stimulation or passive jaw-opening. Abstract: The supratrigeminal nucleus (Vsup), originally proposed as a premotoneuron pool in the trigeminal reflex arc, is a key structure of jaw movement control. Surprisingly, however, the location of the rat Vsup has not precisely been defined. In light of our previous cat studies, we made two hypotheses regarding the rat Vsup: (1) the Vsup is cytoarchitectonically distinguishable from its surrounding structures; (2) the Vsup receives central axon terminals of the trigeminal mesencephalic nucleus (Vmes) neurons which are primary afferents innervating muscle spindles of jaw-closing muscles and periodontal ligaments around the teeth. To test the first hypothesis, we examined the cytoarchitecture of the rat Vsup. The Vsup was identified as an area medially adjacent to the dorsomedial part of trigeminal principal sensory nucleus (Vp), and extended from the level just rostral to the caudal two-thirds of the trigeminal motor nucleus (Vmo) to the level approximately 150 μm caudal to the Vmo. Our rat Vsup was much smaller and its location was considerably different in comparison to the Vsup reported previously. To evaluate the second hypothesis, we tested the distribution patterns of Vmes primary afferent terminals in the cytoarchitectonically identified Vsup. After transganglionic tracer applications to the masseter, deep temporal, and medial pterygoid nerves, a large number of axon terminals were observed in all parts of Vsup (especially in its medial part). After applications to the inferior alveolar, infraorbital, and lingual nerves, a small number of axon terminals were labeled in the caudolateral Vsup. The Vsup could also be identified electrophysiologically. After electrical stimulation of the masseter nerve, evoked potentials with slow negative component were isolated only in the Vsup. The present findings suggest that the rat Vsup can be cytoarchitectonically and electrophysiologically identified, receives somatotopic termination of the trigeminal primary afferents, and principally receives strong termination of the spindle Vmes primary afferents.